Influence of Feeding Compound Feed Rich in Fibre during Parturition and Lactation on Health and Performance of Sows - Cornelia Schwennen; Bernd Reckels; Maria Klingenberg; Amr Abd El-Wahab; Birgit Keller; Christian Visscher (Animals, 2022)
The aim of this study was to investigate the influence of ad libitum access to compound feeds rich in fibre (ante partum (a.p.) and peri partum) on the DM intake, body mass development and performance of sows as well as excretion of Clostridium (C.) perfringens via sows’ faeces. From day 109 (d-7) of gestation, 25 of 48 sows (23 considered as control) received access to one of two different high-fibre pellets from d-7 until the second day post partum (p.p.) (d2) (fibre groups (FG) 1 and 2) in additional to a lactation diet. The additional DM intake of the high-fibre pellets a.p. was 2.13 ± 1.15 kg in FG 1 and 3.14 ± 0.68 kg in FG 2. This led to higher DM intake in the first lactation week and significantly lower losses of weight and back fat thickness during lactation. The bacterial counts of C. perfringens in sows’ faeces directly p.p. were 10 times lower in FG 1 and 100 times lower in FG 2 compared to the controls. High amounts of fibre led to higher DM intake throughout lactation, which had beneficial effects on sows’ body conditions. It seems that high fibre intake influenced the excretion of C. perfringens at parturition, which could improve the health of newborns.